Allah Berperan di Belakang Layar dalam Penderitaan Orang Percaya - Anon Dwi Saputro; Paulus Kunto Baskoro (SANCTUM DOMINE: JURNAL TEOLOGI, 2023)
Suffering is a topic that is often discussed. The suffering that often afflicts humans raises human arguments about the absence of God. They think that if God exists, suffering should not exist. Looking at Exodus 1-2, the narrative does not mention God's name in the suffering the Israelites faced. Through this article, the author will explore how God's role works behind the scenes in people's suffering. The author uses a qualitative method with a narrative interpretation approach to assessing the text. The research question in this study is how is the role of God behind the scenes in the suffering of believers according to theodicy in the narrative of Exodus 1-2? This study aims to find the part of God behind the scenes in the suffering of believers by examining theodicy in the description of Exodus 1-2. This study found that God works behind the scenes for the people through His providence in suffering. Chapter 1 describes God's providence to Israel, and Chapter 2 God's providence to the deliverer. This providence is proof of God's faithfulness to His covenant and shows that His plan must be fulfilled, and nothing can thwart God's plan for His people. It can be concluded that the analysis of the narrative structure of Exodus 1-12 confirms that God works behind the scenes of the people's suffering by organizing the flow of the people's life scenarios in the suffering they face.